Losy ziemiaństwa polskiego w Białoruskiej Sowieckiej Republice Socjalistycznej na obszarze północno-wschodnim dawnych ziem wschodnich Rzeczypospolitej w latach 1921–1939 - Iwanow, Mikołaj (Komunizm: System - Ludzie - Dokumentacja, 2023)
The author demonstrates that the consistent actions of, first, the Tsarist regime and then the Stalinist repressions, whether more or less distant in time, led to the creation of a completely new ethnic situation in the former Borderlands. These actions transformed a large part of the once numerous Polish Borderlandspopulation into a purely historical category of nationality. The author begins his deliberations with the October 1917 Revolution and the rebirth of Polish state, the events of which clearly revived and reinforced the stereotype of the Polish Borderlandsnobility. The author shows that the process of destroying the Polish gentry in the Soviet Union can be conventionally divided into several periods: 1. The period 1925–1927: the period of displacement and confiscation of land for the purposes of the Soviet Bolsheviks’social experiments. The landed gentry was abolished as a social class. 2. The period 1928–1936:the period of the so-called Soviet Polish experiment, related to the establishment of numerous districts of Polish national autonomy. Under these conditions, the repressions against the Polish nobility initially eased somewhat, but soon intensified again in connection with the general drive to collectivisation. 3. The period 1937–1939: this time saw mass displacements of the Polish population and the genocide of Poles during the so-called Polish Operation. The last representatives of the Polish Borderlands nobility were destroyed. The Poles were the first national group to be collectively repressed in the years 1935–1938 solely because of their national affiliation, and not – as had so far been the case – their class affiliation or the allegedly ‘reactionary’ ideological views resulting from this affiliation.